Heinrich Bullinger, political covenantalism and Vermigli’s commentary on Judges - Andries Raath (In die Skriflig, 2005)
The Zurich political federalists under the leadership of Heinrich Bullinger had a number of important views in common: firstly, they subscribed to the ideal of the covenanted nation under God; secondly, they maintained the view that magistrates and their subjects have a covenantal calling to live according to God’s law; thirdly, the binding together (consolidation) of the covenanted Christian polity by means of the oath; fourthly, the right to resistance when the conditions of the covenant are broken; fifthly, the offices of magistrates and pastors are mutually to assist one another in maintaining and furthering the conditions and requirements of the Biblical covenant in the consolidated Christian community. Vermigli used these principles, together with the Chrysostomian and Lutheran views on magisterial office, to develop an influential theory of theologico-political federalism in the Reformational tradition.